The Nature and Function of Digital Information Compression Mechanisms in the Brain and in Digital Television Technology - Smythies, John; de Lantremange, Maximilien d'Oreye (Frontiers in Systems Neuroscience, 2016)
Not applicable to an Opinion Piece